When branding meets innovation: Finding the ideal blend to deliver value. Issue 11 (5th October 2020) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Innovation and branding activities provide the foundation for different strategic positions. Firms that consider resource availability and market conditions can determine an ideal blend of these respective dimensions to optimize value delivered to consumers. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.